PRDH and IMPQ 1800–1849 Quebec Historical Family Reconstitution. Content, Design and Biographical Completeness - Lisa Dillon; Marilyn Amorevieta-Gentil; Alain Gagnon; Bertrand Desjardins (Historical Life Course Studies)
Since 1966, the Programme de recherche en démographie historique (PRDH) has worked to create comprehensive genealogical data of the Quebec population. The PRDH longitudinal database, the Registre de la population du Québec ancien (RPQA), draws upon the French Catholic parish registers of the St. Lawrence Valley as its main source material. This family reconstitution covers the French Catholic population of Quebec up to 1799, along with deaths after 1800 of persons born before 1750. Subsequent partnerships with l’Institut Généalogique Drouin, FamilySearch and Ancestry as well as collaboration on the 2011–2017 Infrastructure intégrée des microdonnées historiques de la population du Québec (1621–1965) (IMPQ) project enabled the PRDH to continue efforts to reconstitute the French Catholic population up to 1849. Despite these advances, pushing family reconstitution forward to the mid-19th century has forced the PRDH team to reckon with the increasingly mixed and geographically mobile Quebec population of the 19th and early 20th centuries. This article describes the content and design of the RPQA database, detailing the structure of the RPQA relational database and the breadth of variables available for data management and analysis. It then describes features of the IMPQ extension of family reconstitution from 1800 to 1849, including observational protocols necessary to use these data and consideration of data completeness after 1800. At the same time, the article addresses the fundamental question, "what is my population?" as part of a broader reflection upon the target population encompassed by these data.